Preparation and properties of PEDOT:PSS/Te nanorod composite films for flexible thermoelectric power generator. (15th April 2017) - Song, Haijun; Cai, Kefeng
Abstract: Poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) functionalized Te (PF-Te) nanorods were in situ synthesized. A simple and efficient vacuum-assisted filtration method was employed to integrate the PF-Te nanorods with PEDOT:PSS to form PEDOT:PSS/PF-Te composite films. By varying the content of PF-Te nanorods, the Seebeck coefficient of the composites increases from 15.6 to 51.6 μV/K, while the electrical conductivity decreases from 1262 to 122.4 S/cm. A maximum power factor of 51.4 μW/mK 2 is obtained from a sample containing 70 wt% PF-Te nanorods at room temperature. An 8 single-leg flexible thermoelectric generator prototype was fabricated using the as-prepared PEDOT:PSS/PF-Te composite film containing 70 wt% PF-Te on a polyimide substrate with Ag electrodes. The prototype produced an output voltage of 2.5 mV at a 13.4 K temperature difference between human body and the environment. Highlights: PEDOT:PSS/Te nanorods composite films were prepared. A vacuum-assisted filtration method was employed to prepare the composite films. A flexible thermoelectric generator composed of the composite film was developed. The generator outputs a voltage of 2.5 mV at a 13.4 K temperature difference.